Comportamiento criminal: elementos históricos y teóricos fundamentales - Cedeño, Viviana A. (2021)
Although it is impossible to study exhaustively the relationship of behavior with crime in the space of a book chapter, it is possible to present its fundamentals as an introductory path to this vast field of study. The present This work provides fundamental historical and theoretical elements on the criminal behavior, from a psycho-legal perspective, useful to understand the incidence of certain factors and conditions in the genesis and development of criminal behavior in humans.